Interactive Digital Multimodal Teaching Materials Based on Socio-Scientific Issues to Improve the Ability to Read Socio-Scientific Texts and Critical Thinking of Elementary School Students - Galih Dani Septiyan Rahayu; Asep Kurnia Jayadinata; Jajang Bayu Kelana (Universitas Negeri Makassar, 2026)
This study analyzes the effectiveness of interactive digital multimodal learning materials based on socio-scientific issues using a rational decision-making learning model on elementary school students' reading ability on socio-scientific and critical thinking skills. One group pretest-posttest design was implemented with three lesson plans. The instrument used was a written test aligned with indicators of reading ability in socio-scientific issues and critical thinking skills. The study sample comprised 76 fifth-grade elementary school students selected through purposive sampling. The results showed an overall increase in students' reading ability on socio-scientific issues and critical thinking skills. This increase occurred because interactive digital multimodal learning materials on socio-scientific issues, using a rational decision-making learning model, encouraged active, collaborative, and interactive learning, enabling students to analyze and evaluate information. Although the absence of a control group requires careful interpretation, these findings highlight the potential of interactive digital multimodal learning materials based on socio-scientific issues in improving reading ability and socio-scientific and critical thinking skills at the elementary school level. This study contributes to language education by supporting pedagogical innovation in facing the challenges of the 21st century.